The Importance of Dividends to Millennial Investors in Indonesian Capital Markets - Said Kelana Asnawi; Dergibson Siagian; Salam Fadilah Alzah; Indra Halim (Jurnal Organisasi dan Manajemen, 2022)
Purpose – This investigation focuses on investors’ interest in cash dividends. In investing selections, dividends are often disregarded, but research on this subject tends to focus on the fundamental variables. Methodology – A questionnaire was submitted to investors on the IDX in October 2021, and 248 data were obtained. The impact of various investor characters, social media and ownership of rumor stocks on the cash dividend were also proposed using logistic regression and multinomial logistic regression. Findings – Except for Genes, none of the other characters indicates an association with/not considering dividends. Only social media variables significantly affect the chances of investors considering dividends. Furthermore, investor experience, risk character and rumor-share ownership variables provide an opportunity to consider dividends below 50%. The results showed that (a) investors who do not follow social media would use cash to buy dividend shares instead of cash withdrawn; (b) Millennials buy other stocks instead of dividend-share; (c) Investors who own rumor stocks will withdraw and purchase others instead of dividend-share. This is because dividends are not considered as an investment strategy. Originality – This study gives (a) a risk-based explanation for investor decisions; (b) behavioral finance research on dividend investing.